PORTRAYAL OF FEMINISM AND MARRIAGE IN ANITA DESAI’S WORKS - Kaur , Komalpreet (International Journal of Psychosocial Rehabilitation, 2020)
For a really long time, ladies in the conventional social request and framework have been thought of as docile 100% of the time to males In a man-centered Bourgeois society, the matriarchal local region has been socially and financially 'embarrassed,' 'beset,' 'hushed,' and 'tormented.' With the post-modern era, women began to experience the world through their own eyes rather than via the male gaze. With the matriarchal struggle against male-dominated society in India, another internal insurgency began to manifest itself through writing, notably women's compositions. The voices of women began to compete with those of men. The purpose of our thesis is to focus on Anita Desai's well-known works, Cry, the Peacock, and Where Shall We Go This Summer?, for their feminist message. Our goal is to look at how Indian female authors in English have addressed women's issues in the post-modern age. They have raised a resounding voice or begun an interior transformation in opposition to traditional values and orientation segregation, with the ultimate goal of balancing common liberties. Considering Anita Desai's femme fatale characters in Cry, the Peacock, and Where Shall We Go This Summer?, maybe the most prominent Indian essayist writing in English, especially the strong and repressive female heroes, Sita and Maya. The purpose of this paper is to draw attention to Desai's functions as model cases of postmodern feminism.